CXCR4 Overexpression is a Poor Prognostic Factor in Pediatric Acute Myeloid Leukemia With Low Risk: A Report From the Japanese Pediatric Leukemia/Lymphoma Study Group. Issue 8 (2nd May 2016) - Matsuo, Hidemasa; Nakamura, Naomi; Tomizawa, Daisuke; Saito, Akiko Moriya; Kiyokawa, Nobutaka; Horibe, Keizo; Nishinaka‐Arai, Yoko; Tokumasu, Mayu; Itoh, Hiroshi; Kamikubo, Yasuhiko; Nakayama, Hideki; Kinoshita, Akitoshi; et al.
Abstract : Background: Overexpression of CXC chemokine receptor 4 ( CXCR4 +) is a poor prognostic factor in adult acute myeloid leukemia (AML); however, its prognostic significance in pediatric AML is unclear. Procedure: This retrospective study examined the prognostic significance of CXCR4 + in pediatric AML patients enrolled in the Japanese Pediatric Leukemia/Lymphoma Study Group AML‐05 study. Results: In the total cohort (n = 248), no significant differences were observed between CXCR4 + patients (n = 81) and CXCR4 − patients (n = 167) in terms of 3‐year overall survival (OS) (69.4% vs. 75.2%, P = 0.44). However, there was a significant difference in 3‐year OS between CXCR4 + and CXCR4 − patients in the low‐risk (LR) group (n = 93; 79.2% vs. 98.3%, P = 0.007). CXCR4 + patients in the t(8;21) AML without KIT mutation group had a significantly worse 3‐year OS than CXCR4 − patients (n = 44; 76.1% vs. 100.0%, P = 0.01). Multivariate Cox regression analysis identified CXCR4 + as a poor prognostic factor for OS in LR AML patients (hazard ratio, 11.47; P = 0.01). Consistent with the data for survival analysis, CXCR4 + patients in the t(8;21) AML group had a higher incidence of splenomegaly than CXCR4 − patients (25.9% vs. 5.9%, P = 0.03). Conclusions: These results suggest that CXCR4 + is a poor prognostic factor for LR patients, particularly t(8;21) patients without KIT mutation. The poor outcome was only applicable to OS, not relapse‐free survival (RFS); thus, CXCR4 + may be associated with a poor prognosis after recurrence. Intensive therapy, including administration of CXCR4 antagonists, may be promising for pediatric AML patients with LR.